Independent Learning Curriculum in School Education Concepts and Planning in Islamic Religious Education Perspective - Ria Mutiani; Ainun Mardiah (AT-TURATS, 2022)
This study tries to describe and analyze the importance of the "Freedom of Learning" curriculum seen from the concept and planning of education at SD Negeri 75 West Pontianak from the perspective of Islamic religious education. Educational "Freedom of Learning" at SD Negeri 75 West Pontianak from the perspective of Islamic religious education. The data were obtained using observation, in-depth interviews, and documentation, following qualitative research procedures. While the analytical technique used was the inductive analysis technique. The results of this study show that in the independent curriculum design, the government emphasizes four programs, namely: USBN, UN, RPP, and PPDB Zoning. SD Negeri 75 Pontianak Barat has prepared itself to participate in innovation following the "Independent Learning" Curriculum program and is currently making preparations and designs regarding this matter. it's like One of them is that the school has provided workshops for teachers so that schools can instill the mindset that the goal of simplifying the RPP does not mean that the special teachers of Islamic Religious Education are lazy, but rather simplifying the RPP so that more teachers can learn.